METHODOLOGY OF TEACHING INFORMATION TECHNOLOGIES IN MEDICINE USING INNOVATIVE TECHNOLOGIES - Normamatov, Sardor Fakhriddinovich; Karaboev , Avazbek Alijonovich (Educational Research in Universal Sciences, 2023)
Reforming the modern system of medical education is aimed at increasing the efficiency of training future doctors who not only have knowledge and skills, but are also ready to apply them in solving problems of professional activity. The authors show the need for biophysics in the future professional activity of a future specialist doctor in solving professional problems.